Phenotyping Post-COVID Pain as a Nociceptive, Neuropathic, or Nociplastic Pain Condition - César Fernández-de-las-Peñas; Jo Nijs; Randy Neblett; Andrea Polli; Maarten Moens; Lisa Goudman; Madhura Shekhar Patil; Roger D. Knaggs; Gisele Pickering; Lars Arendt-Nielsen (Biomedicines, 2022)
Pain after an acute Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection and coronavirus disease 2019 (COVID-19) condition (post-COVID pain) is becoming a new healthcare emergency. Precision medicine refers to an evidence-based method of grouping patients based on their diagnostic/symptom presentation and then tailoring specific treatments accordingly. Evidence suggests that post-COVID pain can be categorized as nociceptive (i.e., pain attributable to the activation of the peripheral receptive terminals of primary afferent neurons in response to noxious chemical, mechanical, or thermal stimuli), neuropathic (i.e., pain associated with a lesion or disease of the somatosensory nervous system and limited to a “neuroanatomically plausible” distribution of the system), nociplastic (i.e., pain arising from altered nociception despite no clear evidence of actual or threatened tissue damage causing the activation of peripheral nociceptors or evidence for disease or lesion of the somatosensory system causing the pain), or mixed type (when two pain phenotypes co-exist). Each of these pain phenotypes may require a different treatment approach to maximize treatment effectiveness. Accordingly, the ability to classify post-COVID pain patients into one of these phenotypes would likely be critical for producing successful treatment outcomes. The 2021 International Association for the Study of Pain (IASP) clinical criteria and grading system provide a framework for classifying pain within a precision pain medicine approach. Here we present data supporting the possibility of grouping patients with post-COVID pain into pain phenotypes, using the 2021 IASP classification criteria, with a specific focus on nociplastic pain, which is probably the primary mechanism involved in post-COVID pain. Nociplastic pain, which is usually associated with comorbid symptomology (e.g., poor sleep quality, fatigue, cognitive–emotional disturbances, etc.) and is considered to be more difficult to treat than other pain types, may require a more nuanced multimodal treatment approach to achieve better treatment outcomes.